THE ROLE OF BRONCHOLOGICAL SANITATION IN THE TREATMENT OF BRONCHIECTASIS - J.S.Hikmatov (Scholar Express Journals, 2024)
Bronchiectasis is a very common condition that is a leading cause of respiratory problems. Treatment methods remain relevant: conservative and surgical. Attempts to give one of them a dominant character did not materialize. Sanitation of the tracheobronchial tree is a therapeutic measure that eliminates the accumulation of mucus on the affected bronchi. The main objectives of sanitation bronchoscopy are to influence the nature of the secretion of the mucous glands, improve the drainage function of the bronchi by removing secretions, and provide anti-inflammatory therapy
Keywords: Bronchiectasis; inflammation; sanitation bronchoscopy